Implementation of Reading Fixed ˜Do™ and Moving ˜Do™ Notations on Improving Music Practical Achievement - Murbiyantoro, Heri; Dharmawanputra, Budi; Anggoro, Raden Roro Maha Kalyana Mitta; Karyawanto, Harpang Yudha; Mahendra, Marda Putra (Gondang: Jurnal Seni dan Budaya, 2024)
Music education is a realm of study concerned with the teaching and learning of music. This music education will develop affective, motor skills in students who play instruments and expand cognitive development through reasoning and interpretation of musical notation. However, many people still underestimate music education. In the education and teaching system of music arts, especially in the last years of the 20th century, new methods emerged. One of the methods that will be discussed is the Tonika-Do Method. This article is a type of literature study and uses the exposition method in presenting the concepts contained in previous studies. The sources used contain the results of discussions about art education, music, and music education. The application of fixed "do" is not carried out as it should be from the meaning of fixed "do" itself. The reading system used in this lesson is not an fixed "do", but a system taken from the basic idea of an fixed "do" system, where 'Do' is not understood as a C, D, E note or something else, but is more understood as a number 1, which is the tone of writing in numerical notation. This fixed œdo reading system is carried out with the aim of avoiding moving 1 ('do') which is generally found in how to read numerical notation, which of course tends to make it difficult for students in a notation recognition. The learning process can include practicing the C scale, followed by the chromatic scale, etude, then entering the song.